Sonolithography: In‐Air Ultrasonic Particulate and Droplet Manipulation for Multiscale Surface Patterning. Issue 3 (2nd December 2020) - Shapiro, Jenna M.; Drinkwater, Bruce W.; Perriman, Adam W.; Fraser, Mike
Abstract: Acoustic fields are increasingly being used in material handling applications for gentle, noncontact manipulation of particles in fluids. Sonolithography is based on the application of acoustic radiation forces arising from the interference of ultrasonic standing waves to direct airborne particle/droplet accumulation in defined spatial regions. This approach enables reliable and repeatable patterning of materials onto a substrate to provide spatially localized topographical or biochemical cues, structural features, or other functionalities that are relevant to biofabrication and tissue engineering applications. The technique capitalizes on inexpensive, commercially available transducers and electronics. Sonolithography is capable of rapidly patterning micrometer to millimeter scale materials onto a wide variety of substrates over a macroscale (cm 2 ) surface area and can be used for both indirect and direct cell patterning. Abstract : Sonolithography is an in‐air acoustophoretic technique based upon acoustic radiation forces generated by ultrasonic standing waves. An octagonal array producing four standing waves is used to focus and manipulate liquid droplets and solid particles of a variety of materials on various substrates. A size‐dependent localization is observed. Sonolithography's potential in biofabrication is illustrated through indirect and direct cell patterning.